Long‐term effect of gender‐affirming hormone treatment on depression and anxiety symptoms in transgender people: A prospective cohort study. (3rd September 2020) - Aldridge, Zoë; Patel, Shireen; Guo, Boliang; Nixon, Elena; Pierre Bouman, Walter; Witcomb, Gemma L.; Arcelus, Jon
Abstract: Background: Cross‐sectional studies show that transgender people are more likely than cisgender people to experience depression and anxiety before gender‐affirming hormone treatment (GAHT). However, the effect of GAHT on mental health in transgender people, and the role of other factors that may have a predictive effect, is poorly explored. Objectives: Using a longitudinal methodology, this study investigated the effect of 18‐month GAHT on depression and anxiety symptomatology and the predictors on mental health outcomes in a large population of transgender people. Materials and methods: Participants (n = 178) completed a socio‐demographic questionnaire, the Hospital Anxiety and Depression Scale (HADS), the Multidimensional Scale of Perceived Social Support (MSPSS) and the Autism Spectrum Quotient—Short Version (AQ‐Short) at pre‐assessment (T0) and at 18 months after initiation of GAHT (T1). Results: From T0 to T1, symptomatology was significantly decreased for depression ( P  < .001) and non‐significantly reduced for anxiety ( P  = .37). Scores on the MSPSS predicted reduction in depression, while scores on the AQ‐Short predicted reduction in anxiety. Discussion: GAHT reduces symptoms of depression which are predicted by having higher levels of social support. Although anxiety symptoms also reduce, the changes are not significant and high levels of anxiety still remain post‐GAHT. Conclusions: These results highlight the important mental health benefits of GAHT. Support services (professional, third sector or peer support) aiming at increasing social support for transgender individuals should be made available.